KRITIK SOSIAL DALAM NOVEL O KARYA EKA KURNIAWAN: KAJIAN SOSIOLOGI SASTRA - Agus Imam (LPPM UNISDA, 2017)
This research was conducted with the aim to describe the social criticism in the novel O created Eka Kurniawan. The research data was sourced from the novel O created Eka Kurniawan and social context derived from newspaper reports that support the understanding of social criticism. Data collected by the method of the literature, see, and record. This research uses a sociological study of literature using heurmeneutic and mimesis. The results of research showed the researcher criticism to ward, rape, and social indifference. The finding people's lives are very selfish. What stands out is indifference. That is done only to eat each other to survive. While the animals instead of mutual help and advise in terms of goodness. Supposedly people can learn the virtues even though it was done by an animal. It was concluded that all forms of torture, rape, and social indifference is painful. It was not expected to occur again in the community.